Are Reported Greenhouse Gas Emissions Influencing Corporate Financial Performance? - Elena-Mirela Nichita; Elena Nechita; Cristina-Lidia Manea; Alina Mihaela Irimescu; Diana Manea (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - This paper aims to analyse the impact of reported greenhouse gas (GHG) emissions on financial performance of companies operating in the chemical industry from Central-Eastern Europe over the period 2015-2019. Motivation - Currently, the climate change and global warming have become highly topical due to their progressively visible destructive effects worldwide on the environment, society, and economic activity. Idea - To offer the suitable information to all its stakeholders, each company should identify the necessary information, measure it, make it useful, and take reasonable steps to ensure that it's accurate; our research investigates the effect of reported greenhouse gas emissions on return on sales, as a measure of business performance. Data - The paper is based on panel data extracted from non-financial and/or annual reports for the top 10 largest companies operating in the chemical industry geographically located in Central-Eastern Europe covering the time frame 2015-2019. The final sample consists of 34 firms and 134 firm-year observations. Tools - A multiple linear regression model was designed and applied, having return on sales as the dependent variable and GHG emissions as the independent variable. Findings - The findings of our study confirm that a lower level of GHG emissions will generate an increase in return on sales, consequently, the environmental performance reported in terms of controlling for GHG emissions enhances the financial performance measured as return on sales ratio. Contribution - The paper contributes to the literature on climate change, revealing a negative, but significant effect of GHG emissions on financial performance and endorsing that companies which today pay less attention to this global concern, tomorrow will face difficulties in terms of sales.
Keywords: M41; Q01; Q54; 650; GHG emissions; return on sales; climate change; environmental performance; financial performance; Central-Eastern European countries (CEE countries); stakeholders